Intensified Humid Heat Events Under Global Warming - Pinya Wang; Yang Yang; Jianping Tang; L. Ruby Leung; Hong Liao (Geophysical Research Letters)
Abstract Based on the Coupled Model Intercomparison Project Phase 5 multimodel simulations, this paper investigates the future changes in extreme wet‐bulb temperatures (TWs) and extreme dry‐bulb temperatures (Ts) globally under both low‐emission and high‐emission scenarios (Representative Concentration Pathways of 4.5 [RCP4.5] and 8.5 [RCP8.5]). Under a warming climate, T and TW exhibit a higher absolute increase in their mean values over the mid–high latitudes while they show higher relative increases in their mean values and variability over tropics. Humid and dry heat events which consist of consecutive extreme TWs and Ts show higher occurrences over tropics, governed by the joint increases in mean values and variability of TW and T therein. Humid heat events show intensifications to dry heat events with higher frequency, duration, and intensity, driven by the lower variability of TW than T. In the mid–high latitudes, heat events will start earlier and last longer in warm season under RCP8.5 than RCP4.5, motivating the need for global warming mitigation.